PENGARUH DIRECT CORRECTIVE FEEDBACK TERHADAP HASIL BELAJAR PADA MATERI pH ASAM BASA SMK - Destarika, Tiara; Melati, Husna Amalya; Hadi, Lukman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe aims of this study was to determine the influence of Direct Corrective Feedback towards learning outcomes of class XI grade students of SMK Negeri 02 Pontianak on acid base potential hydrogen subject material. This research was used quasi experimental with nonequivalent control group design. Population in this study was XI SMK Negeri 02 Pontianak. The research samples were XI grade of TSM (Teknik Sepeda Motor)’s class control and XI grade of TP (Teknik Pemesinan)’s class experimental. Pretest-posttest, questionnaire , observation sheet and interview guide lines were used to collect data. On the ability of the students there have been the difference, then process is gain score based on results of normality the data berdistribusi. The learning were analyzed using T-test (independent samples T-test) that there were a significant difference between students learning dirrect corrective fedback modelland conventional learning model. Based on the calculation effect size obtained 3,7 point with high category. The conclusion in this research are the difference a dirrect corrective fedback XI SMK Negeri 02 Pontianak on acid base material has of 49,89% effect on improving students achievement.                                                   Keywords: Direct Corrective Feedback, quis, pH acid base